NEXUS OF ESG DISCLOSURE, SUSTAINABILITY PERFORMANCE AND FINANCIAL PERFORMANCE ON FIRM VALUE: THE ROLE OF CORPORATE REPUTATION AND SUSTAINABILITY REPORTING QUALITY - Сіті Нурлатіфа; Трі Відястуті; Нурмала Ахмар (Фінансово-кредитна діяльність: проблеми теорії та практики, 2025)
This research aims to explore how the disclosure and performance on the ESG aspect are related to the firm's value, with corporate reputation possibly acting as the mediating variable in such relations, while the sustainability reporting quality serves as a moderating variable. The samples used in this research are ESG SRI KEHATI index companies collected from IDX during 2017-2022. For that, the present study has taken purposeful sampling methods where a sum of 19 firms was taken and their total number of observations accounts for 114 observations. The regression analysis of these factors shows that ESG disclosure along with sustainability and financial performance in giving reputation to the corporation results in high significance on corporate values. Corporate reputation successfully mediates the relationship of ESG disclosure and sustainability performance with financial performance on corporate value. Meanwhile, sustainability reporting quality only moderates the relationship of ESG disclosure, sustainability performance, and financial performance towards corporate value but does not moderate the relationship of the variables towards corporate reputation. This in practice means that this research shows that managers have to improve the quality of sustainability reporting, while one should build a corporate reputation by being responsible and transparent in business conduct. The current paper develops the signalling theory and the resource-based theory for accounting and sustainability.